2009
DOI: 10.3171/2009.3.jns081285
|View full text |Cite
|
Sign up to set email alerts
|

Decreased brain edema after collagenase-induced intracerebral hemorrhage in mice lacking the inducible nitric oxide synthase gene

Abstract: When hematoma size was similar, iNOS knockout mice had significantly less brain edema than their littermates. These results suggest that iNOS modulation might become an antiedematous therapy for ICH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…The neuroprotection by atorvastatin or bortezomib was associated with the inhibition of iNOS induction after ICH [23,24]. Moreover, iNOS knockout mice had significantly less brain edema in a collagenase-induced ICH model [3]. The iNOS-derived NO can exert injurious effects by several mechanisms, one of which is the activation of MMP-9, causing neuroinflammation, cell death, and the blood-brain barrier (BBB) disruption [2,25,26].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The neuroprotection by atorvastatin or bortezomib was associated with the inhibition of iNOS induction after ICH [23,24]. Moreover, iNOS knockout mice had significantly less brain edema in a collagenase-induced ICH model [3]. The iNOS-derived NO can exert injurious effects by several mechanisms, one of which is the activation of MMP-9, causing neuroinflammation, cell death, and the blood-brain barrier (BBB) disruption [2,25,26].…”
Section: Discussionmentioning
confidence: 98%
“…However, the data on the pathogenesis of ICH-induced brain injury are still limited, although matrix metalloproteinases (MMPs) have received special attention as contributors to brain damage produced by ICH [2]. A recent study showed that inducible nitric oxide synthase (iNOS) knockout mice had significantly less brain edema in a collagenase-induced ICH model [3]. Nitric oxide (NO) produced by iNOS is known to activate MMP-9 [2].…”
mentioning
confidence: 99%
“…Investigators of other studies 42,j found that administration of an inhibitor of inducible NO synthase reduces neurologic deficits but not cerebral edema, which appears to be a consequence of traumatic brain damage. Analysis of the results of this and other studies [40][41][42] does not support a direct role of NO in brain edema formation.…”
Section: Discussionmentioning
confidence: 51%
“…Numerous studies [39][40][41] have been performed on mammals to determine associations of increased BBB permeability and the appearance of cerebral edema with increased NO synthesis. In the study reported here, a time connection existed between the total serum nitrate and nitrite concentration in carp and BBB permeability (degree of intensity of staining with Evans blue dye) as well as between the total serum nitrate and nitrite concentration and brain edema formation.…”
Section: Discussionmentioning
confidence: 99%
“…iNOS protein was not detectable until 24 h post ICH and reached the peak at 3 days after ICH (Zhao et al, 2007). iNOS knockout decreased brain edema at 3 day post ICH (Kim et al, 2009). Hemoglobin infusion into striatum increased eNOS levels and NO production (Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%